Moringa leaf meal as natural feed additives on the growth performance and meat quality of commercial broiler chicken - Sarker, Md Sazedul Karim; Rana, Md Masud; Khatun, Halima; Faruque, Shakila; Sarker, Nathu Ram; Sharmin, Farhana; Islam, Md Nazrul (Asian Journal of Medical and Biological Research, 2017)
A study was conducted to investigate the effect of dietary moringa leaf meal (MLM) as a natural alternative to antibiotic on the growth performance, meat quality and carcass yield of broiler chicken. A total of 270 day-old broiler chicks were randomly weighed and assigned to six dietary treatments having 45 birds in each. Each dietary treatment had three replicates of 15 birds and was reared in floor pens. Chicks were distributed in 4 different inclusion levels of MLM in diets; 0.5%, 1.0%, 1.5% and 2.0% with 2 control diets negative and positive. The birds were fed the experimental diets and water was provided without restriction throughout the experimental period. The results showed that significant (P<0.05) effect on final body weight and weight gain in dietary supplementation of 1.5% MLM as compared to that of control group. Better feed conversion (1.53) was observed at 1.5% MLM group. Different levels of MLM exhibit significant influence on meat yield performance of broilers. There was no significant difference (P>0.05) observed among the average live weight, thigh meat, wing meat, drumstick meat, gizzard and abdominal fat of broilers. Breast meat, heart, liver, large intestine and dressing percentage showed significant difference. Lower mortality was found on diet supplemented with MLM. It is concluded that 1.5% MLM in broiler diets can be used as natural feed additive for enhancing growth performance, organ development, meat yield and serum cholesterol of broilers as well as replacing of oxytetracycline. Asian J. Med. Biol. Res. June 2017, 3(2): 240-244